BIOM-60. BIOMARKER EVALUATION FOR IMIPRIDONE ONC206 REVEALS ClpP, ATF4, MYC, EGFR and HIF1 AS KEY PREDICTORS OF ANTI-CANCER EFFICACY - Morrow, Sara (Neuro Oncol, 2020)
ONC206 is a DRD2 antagonist and ClpP agonist that is a chemical derivative of ONC201, which is in Phase II clinical trials for H3 K27M-mutant glioma. We have previously reported that dopamine receptor expression correlates with ONC201 and ONC206 efficacy. Here, we evaluated additional predictive biomarkers for both agents in the GDSC panel using RNA-seq expression data. ClpP emerged as a strong predictor of efficacy for ONC206 (IC50: p = 1.83E-4, AUC: 9.92E-13). ClpP activation enhances degradation of its substrates, including electron transport chain members responsible for oxidative phosphorylation (OXPHOS). Imipridones activate the integrated stress response involving ATF4 and cause proteasomal degradation of c-myc, which also reduces OXPHOS. Accordingly, high ATF4 (IC50: p = 4.92E-5, AUC: p=2.84E-9) and elevated c-myc correlated with ONC206 efficacy (IC50: p = 6.42E-6, AUC: 3.31E-12). EGFR expression is inversely correlate with DRD2 expression in glioma and its activation is associated with glycolysis. Low EGFR expression correlated with increased ONC206 efficacy (IC50: p = 4.32E-7, AUC: p = 6.44E-20). Loss of HIF1 shunts cellular metabolism toward OXPHOS. Low HIF1 expression correlated with increased anticancer efficacy for ONC206 (IC50: p = 1.96E-3, AUC: p = 1.56E-11). Expression of each of the five markers was significantly different in cell lines that achieved an IC90 with ONC206 (~10%) versus those that did not. A similar analysis for ONC201 revealed that ClpP, MYC and EGFR are more predictive of efficacy relative to ATF4 and HIF1. Combinatorial biomarker analyses revealed MYC/EGFR as the most significant predictor of IC50 for both agents. ClpP/MYC and ClpP/HIF1 were the most significant predictors of AUC for ONC201 and ONC206, respectively. Ongoing studies are further investigating tumor type enrichment of biomarkers. Prediction of innate imipridone sensitivity using biomarkers identified in this study may guide patient and tumor type selection in clinical trials.